Response of Protective Enzymes in Western Flower Thrips (Thysanoptera: Thripidae) to Two Leguminous Plants. Issue 5 (14th August 2020) - Liu, Li; Hou, Xiao-Lin; Yue, Wen-Bo; Xie, Wen; Zhang, Tao; Zhi, Jun-Rui
Abstract: The western flower thrips, Frankliniella occidentalis, is a major invasive pest of commercially important crops worldwide. We compared the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) and the expressions of two putative SOD and two putative POD sequences in second instar larvae and adults after three generations of adaptation to kidney bean and broad bean plants. The results showed that the SOD, POD, and CAT activities in adults were significantly higher than those in the second instar larvae. The SOD activities were significantly higher in both the second instar larvae and the adults fed on kidney bean (Phaseolus vulgaris) plants versus broad bean (Vicia faba) plants, whereas the POD and CAT activities showed the opposite trend. The gene expression data showed that the FoPOD-2 expression levels were lower in the second instar larvae after three generations of feeding on broad bean plants versus kidney bean plants. The expression levels of FoSOD-1 and FoSOD-2, and FoPOD-1 under broad bean plant treatment were higher than those under kidney bean plant treatment. Additionally, gene expression fluctuated among the different generations. Our results indicated that western flower thrips demonstrated plasticity in gene expression and activity of protective enzymes, which is related to their adaptability to the host plants. Western flower thrips can change the expression of protective enzyme genes and enzyme activity in vivo to better adapt to kidney bean and broad bean plants.